Subcutaneous emphysema of the neck, chest, and abdomen as a symptom of colonic diverticular perforation into the retroperitoneum - Janczak, Dariusz; Ziomek, Agnieszka; Dorobisz, Tadeusz; Dorobisz, Karolina; Janczak, Dawid; Pawłowski, Wiktor; Chabowski, Mariusz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2016)
We describe a rare case of a patient with colonic diverticular perforation manifested only by subcutaneous emphysema of the neck, chest, and abdomen, as visualized by a computed tomography (CT) scan. The 76-year-old female patient with a history of internal diseases was urgently admitted to the Clinic of Internal Diseases due to a urinary tract infection. During the hospitalization, further diagnostic procedures were performed due to palpable subcutaneous emphysema of the neck, chest, and abdomen. Computed tomography examination revealed massive intra-abdominal, intramuscular, and subcutaneous emphysema. A decision was made to perform exploratory laparotomy; the procedure exposed an inveterate diverticular perforation of the sigmoid-rectal flexure as well as air-inflated retroperitoneal tissue. The perforated colon was resected, and a stoma was formed. On the 15th postoperative day, the patient died due to cardiorespiratory failure. Although subcutaneous emphysema is a common symptom in everyday medical practice, its etiology remains complex. One should consider this clinical presentation of colonic diverticular perforation, especially in elderly patients in whom the perforation signs may be clinically less marked.